4‐3: Late‐News Paper: OLED Device Technologies for Automotive Application. Issue 1 (25th September 2020) - Mori, Shigeru; Hamada, Keita; Hanashima, Hiromu; Shimoda, Masamichi; Yanase, Jiro; Matsueda, Yojiro; Tanabe, Hiroshi
Abstract : We have demonstrated an OLED display with the high luminance of 1000 nit and long lifetime of LT80 > 1000 hours at 85°C for automotive application. Our display features a highly stable EIL/ETL structure at high temperature and low angular colorshift technology for red emission.